What are You Looking at? - Peter Bentley (Opticon1826, 2007)
You’re waiting at the station for your train and you glance at the electronic poster next to you. It notices that you’re looking at it, and from your gaze it works out what you would most like to see. The display changes to show you new brands of mobile phone, and then changes again to show handheld computers as it notices your gaze flicker. You glance at the clock and so it brings up a list of forthcoming trains, then zooms in on yours and shows you exactly how long it will take to arrive. It’s as though it’s reading your mind – but really it’s reading your eyes.
Keywords: neural networks; support vector machines; eye movement